Pengaruh Kualitas Produk, Brand Image, dan Promosi Terhadap Keputusan Pembelian pada E-Commerce Shopee: Studi Empiris pada Konsumen E-Commerce Shopee Kabupaten Demak - Umi Nandhifatul Muna; Mulyo Budi Setiawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Determining the impact of advertising, brand image, and product quality on Shopee e-commerce purchase decisions is the goal of this study. The Demak Regency's e-commerce clientele is the subject of this study; nevertheless, the precise population estimate is unknown. One hundred respondents were chosen for the sample using the target sampling technique. The hypothesis was tested using multiple linear regression analysis, and its validity was assessed using the F and t tests. The findings of the study indicate that: (1) brand image has no influence on purchasing decisions; (2) product quality has a positive and substantial effect on purchasing decisions; and (3) promotion has a positive and significant effect on purchasing decisions.